Time-resolved diffraction with an optimized short pulse laser plasma X-ray source - M. Afshari; P. Krumey; D. Menn; M. Nicoul; F. Brinks; A. Tarasevitch; K. Sokolowski-Tinten (Structural Dynamics, 2020)
We present a setup for time-resolved X-ray diffraction based on a short pulse, laser-driven plasma X-ray source. The employed modular design provides high flexibility to adapt the setup to the specific requirements (e.g., X-ray optics and sample environment) of particular applications. The configuration discussed here has been optimized toward high angular/momentum resolution and uses Kα-radiation (4.51 keV) from a Ti wire-target in combination with a toroidally bent crystal for collection, monochromatization, and focusing of the emitted radiation.